Contextualization of the Ethics of the Prophet Muhammad's Preaching from the Perspective of Qur'ani (Interpretation in the Digital Age) - Siti Lailatul Atiah; Ahmad Isnaeni; Suhandi Suhandi (Insitut Muslim Cendekia, 2025)
This study aims to contextualize the ethical principles of the Prophet Muhammad’s da‘wah as articulated in Q.S. An-Nahl [16]:125, Q.S. Ali Imran [3]:104, and Q.S. Fussilat [41]:33 through a comparative analysis of Tafsir Al-Maraghi and Tafsir Al-Misbah, and to examine their relevance to contemporary digital da‘wah practices. Employing a qualitative descriptive method with a literature-based inquiry, this research analyzes classical and modern exegetical sources. The findings demonstrate that the three core principles of Islamic propagation bil hikmah, al-mau‘izhah al-hasanah, and al-mujādalah billatī hiya aḥsanretain strong applicability within today’s digital environment, which is characterized by rapid information flow, high interactivity, and susceptibility to misinformation and polarization. Both tafsirs emphasize wisdom, moral exemplarity, and constructive dialogue as ethical foundations of a humanistic and adaptive approach to da‘wah. This study concludes that Qur’anic ethics serve not only as a normative framework but also as a practical guide to uphold integrity in digital religious communication. The results imply the necessity of digital da‘wah ethics literacy among preachers so that religious messages can be delivered accurately, responsibly, and for the public good.